The Analysis of Consumer Satisfaction in Airlines Industry - Zaharias, Bryan Mikail (RIEBS, 2016)
Abstract:This study examines the factors that determine airlinesâ customer satisfaction rating, according to SKYTRAX in which SKYTRAX is a world airline audit that leads product and service quality improvement program for the airline industry with 26 years of experience. SKYTRAX audit the performance of the airlines through customer reviews and rate them with 1-5 and 1-10 interval Likert scale. This study uses only 3 variables from SKYTRAX which are food and beverages, seat comfort, staff service, and number of reviews that act as a control variable. This study uses ordered probit regression model because the data are cross section and the dependent variable is discrete variable (1-10 Likert scale). The number of airlines observed is 128. The result reveals that Food and Beverages, Seat Comfort and Staff service have positive significant effect on increasing the probability of an airline getting a higher rating, which means more satisfied customer.Keywords: Airline studies, airlines rating, SKYTRAX, airline industry, customer satisfaction, ordered probit model